Seasonal Patterns in Growth Hormone, Insulin and Insulin-like Growth Factor-1 in Female Muskoxen - Adamczewski, Jan Z.; Tedesco, Susan C.; Laarveld, Bernhard; Flood, Peter F. (Rangifer, 1997)
Over a year, mean serum growth hormone concentrations ranged from 0.5 to 3 ng/ml in tame muskoxen with the lowest values and fewest pulses between October and January. Serum insulin ranged from 0.25 to 0.92 ng/ml, with minima in summer. There were marked seasonal changes in serum insulin-like growth factor-1 in both tame and wild muskoxen but the late summer peak was higher and more distinct in the tame animals with levels reaching 160-250 ng/ml in September.
Keywords: Ovibos moschatus; nutrition; weight; muskoxen; hormones